Oxygen Saturation (SPO2) in Covid-19 Patients - Ulfa Husnul Fata; Lutvi Febriana (Journal of Ners and Midwifery, 2021)
One of the emergency problems of Covid-19 patients is a decrease in oxygen saturation (SpO2). Factors that affect the decrease in oxygen saturation, age, immune system, and gender. The purpose of this study was to identify Oxygen Saturation (SpO2) in Coronavirus Disease (Covid-19) patients. The research design is descriptive. The population in this study were all Covid-19 patients at the Aminah Blitar Islamic Hospital starting last month December 2020 to March 2021 totaling 346 and the number of samples is 185. This research instrument uses data studies on the medical records of Covid-19 patients. Sampling technique using purposive sampling. Statistic testusefrequency distribution. The results of this study indicate that from 185 respondents there were 77 (41.4) respondents who did not experience hypoxemia and 108 (58.6) respondents experienced hypoxemia. Covid-19 must be watched out for because of its relatively fast transmission, has a mortality rate that cannot be ignored, and there is no definitive therapy yet. A decrease in oxygen saturation (SpO2) is an important thing that needs to be considered in Covid-19 patients.